The relationship between self-confidence and mathematical reasoning ability of grade XI students in sequences and series - Rani Melinda; Rika Mulyati Mustika Sari; Rafiq Zulkarnaen (AXIOM : Jurnal Pendidikan dan Matematika, 2026)
Mathematical reasoning ability is one of the essential hard skills students need, especially for solving real-world problems. Self-confidence is defined as a state in which individuals feel comfortable with themselves, are willing to act decisively, recognize their own worth and competence, and accept themselves as they are. This study aims to examine the relationship between self-confidence and the mathematical reasoning ability of eleventh-grade high school students on the topic of sequences and series, as well as the contribution of self-confidence to their mathematical reasoning ability. This study employed a quantitative approach using a correlational design with an ex post facto method. The population consisted of 163 eleventh-grade students, from which a sample of 62 students was selected using simple random sampling. The research instruments included an essay test on mathematical reasoning and a self-confidence questionnaire. The data were analyzed using a correlation test. The results showed a weak positive relationship between self-confidence and mathematical reasoning ability (ρ = 0.365). The self-confidence questionnaire revealed that 48% of the students had low self-confidence, 34% had moderate self-confidence, and 17% had high self-confidence. Furthermore, 76% of the students scored below the Minimum Passing Criteria, while only 24% scored above it. Therefore, the relationship between self-confidence and the mathematical reasoning ability of eleventh-grade high school students on the topic of sequences and series is weak.